Rattus timorensis Kitchener, Aplin, and Boeadi 1991 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus timorensis Kitchener, Aplin, and Boeadi 1991 Rattus timorensis Kitchener, Aplin, and Boeadi 1991, Rec. West. Aust. Mus., 15: 446. Type Locality: Indonesia, Nusa Tenggara, Timor, Gunung Mutis, 1900 m, 7 km E Desa Nenas. Vernacular Names: Timor Forest Rat. Distribution: Known only from the type locality. Conservation: IUCN – Data Deficient. Discussion: Rattus species-group unresolved. Represented only by the holotype. Some of the large series of subfossil fragments collected in E Timor by Glover (1986) may be this species. Phylogenetic affinities unknown and possibly not even a member of Rattus (Kitchener et al., 1991 b ). Albumin immunological analysis suggests a close phyletic affinity with Bunomys chrysocomus from Sulawesi and Komodomys rintjanus from Nusa Tenggara (Watts and Baverstock, 1994 b ); the close alliance between rintjanus and timorensis , and their great phylogenetic distance from Rattus , is supported by a recent unpublished allozyme electrophoresis study (K. Aplin, in litt., 2004). Recently, K. Helgen (in litt., 2003) collected an extant specimen from a forest fragment on Timor that is not R. timorensis , but an undescribed species that is also represented by large series in Glover’s subfossil collections. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1491, DOI: 10.5281/zenodo.7316535